Synchronous Current Compensator for a Self-Balanced Three-Level Neutral Point Clamped Inverter. (29th April 2014) - Krishna, Remya; Soman, Deepak E.; Kottayil, Sasi K.; Leijon, Mats
Abstract : This paper presents a synchronous current control method for a three-level neutral point clamped inverter. Synchronous reference frame control based on two decoupled proportional-integral (PI) controllers is used to control the current in direct and quadrature axes. A phase disposition pulse width modulation (PDPWM) method in regular symmetrical sampling is used for generating the inverter switching signals. To eliminate the harmonic content with no phase errors, two first-order low pass filters (LPFs) are used for thed q currents. The simulation of closed-loop control is done in Matlab/Simulink. The Vertex-5 field programmable gate array (FPGA) in Labview/CompactRio is used for the implementation of the control algorithm. The control and switch pulse generation are done in independent parallel loops. The synchronization of both loops is achieved by controlling the length of waiting time for each loop. The simulation results are validated with experiments. The results show that the control action is reliable and efficient for the load current control.